2012
DOI: 10.1111/lcrp.12002
|View full text |Cite
|
Sign up to set email alerts
|

Early maladaptive schemas in relation to facets of psychopathy and institutional violence in offenders with personality disorders

Abstract: Purpose. Current knowledge suggests that the psychopathy construct is multifaceted in nature, and reflects different underlying pathological mechanisms, including neurobiological dysfunction and maladaptive cognitions. Although many contemporary studies focus on neurobiological aspects of psychopathy, few have addressed the maladaptive cognitions.Method. In this study, we examined facets of Hare's psychopathy construct in terms of their associations with maladaptive cognitions, as defined by Young's cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 85 publications
(114 reference statements)
0
38
0
2
Order By: Relevance
“…In a community forensic mental health sample, Gilbert et al () found that higher levels of Insufficient Self‐Control was independently related to a greater history of past aggression ( β = 0.35). Contrary to the above findings, Chakhssi, Bernstein, and De Ruiter () found that in a sample of male offenders meeting Diagnostic and Statistical Manual of Mental Disorders–Fourth Edition PD diagnostic criteria, EMSs were not independently associated with institutional violence.…”
Section: Introductionmentioning
confidence: 73%
“…In a community forensic mental health sample, Gilbert et al () found that higher levels of Insufficient Self‐Control was independently related to a greater history of past aggression ( β = 0.35). Contrary to the above findings, Chakhssi, Bernstein, and De Ruiter () found that in a sample of male offenders meeting Diagnostic and Statistical Manual of Mental Disorders–Fourth Edition PD diagnostic criteria, EMSs were not independently associated with institutional violence.…”
Section: Introductionmentioning
confidence: 73%
“…However, the affective dimension has neither been shown to predict institutional violence in male offenders (Chakhssi et al, 2014;Walters & Heilbrun, 2010) nor to be associated with frequent physical fights in adulthood (Hall et al, 2004).…”
Section: Dimensional Construct Of Psychopathymentioning
confidence: 98%
“…In forensic samples, the content and nature of EMSs have been reliably assessed via selfreport methodology. A considerable amount of research (e.g., Calvete, 2008;Chakhssi et al, 2012;Gilbert & Daffern, 2013;Specht, Chapman, & Celluci, 2009) found a positive association of mistrust/abuse, insufficient self-control and entitlement schemas with antisocial behavior. It is noteworthy that entitlement can also develop as an overcompensation for failure and defectiveness/shame schemas (Rafaeli et al, 2011).…”
Section: Introductionmentioning
confidence: 99%